Molecular targets for metastasis-directed therapy in malignant tumors - V. V. Bodenko; M. S. Larkina; A. A. Prach; E. V. Plotnikov; M. V. Belousov; V. I. Chernov (Бюллетень сибирской медицины)
Over the past two decades, targeted therapy has actively developed and, demonstrating impressive clinical results, has gained an increasingly important role in the treatment of cancer. This was facilitated to a large extent by an in-depth understanding of the mechanisms of cancer development, and mainly, the discovery of molecular targets. Despite the fact that targeted therapy can radically change the results of treatment and the prognosis of the disease course in some cancer cases, its effectiveness is sometimes replaced by drug resistance, in others. The authors of the lecture analyzed and systematized therapeutic approaches to addressing a number of important molecular targets that are key for implementing a specific stage in human tumor pathogenesis. These include maintaining chronic proliferative signaling, promoting evasion of cell growth suppressors, inducing angiogenesis, forming immune surveillance, and activating invasion and metastasis. The lecture presented targeted therapy drugs used in the Russian Federation, including antibody-based drugs and small molecule tyrosine kinase inhibitors. It also analyzed mechanisms of molecular interaction between these drugs and their targets, as well as possible factors for developing resistance and ways to overcome these resistance mechanisms.